Jacopo Strada and Cultural Patronage at The Imperial Court (2 Vols.) The Antique as Innovation - Jacob Jansen, Dirk (Rulers & Elites, 2019)
Dirk Jacob Jansen provides an overview of the life and career of the sixteenth-century cosmopolitan courtier, architect and antiquary Jacopo Strada. Readership: All interested in Austrian and Italian Renaissance archtecture, art and antiques trade, court life, and the transmission of ideas to North and Central Europe.